Recycled HDPE reinforced with sol–gel silica modified wood sawdust. (March 2016) - Brostow, Witold; Datashvili, Tea; Jiang, Peter; Miller, Harrison
Graphical abstract: Compatibility between the polymer matrix and wood fiber cells was achieved using a novel chemical modification process. Modification also promotes filling of the wood fiber cells with the silica nanoparticles and formation of the silica rods is seen; as a result we have improved mechanical and tribological properties of high density polyethylene while finding use for wood sawdust. Highlights: We have improved mechanical and tribological properties of high density polyethylene while finding use for wood sawdust. Silica nanoparticles are filling wood fiber cells and silica rods are formed. With one exception, residual depth in scratch resistance testing decreases as a consequence of introduction of the fillers. Addition of unmodified wood results in increasing dynamic friction, chemical modification of wood particles results in lowering friction. Abstract: The goal of the work was improvement of mechanical and tribological properties of high density polyethylene (HDPE) while finding use for wood sawdust (wood flour). Two chemical modification methods have been used for wood sawdust treatment to improve compatibility between the HDPE matrix and wood sawdust. Traditional silane coupling was used as a first approach to modify the sawdust by 3-methacryloxypropyl-trimethoxysilane (3MPS) and thereby forming COSi bonds. As a second method, we decided to combine sol–gel process with 3MPS treatment to form SiOSi and COSi linkages. Silica nanoparticles are filling wood fiber cells and silica rods formation is seen; as a result, thermal expansivity decreases. As expected, the enthalpy of fusion and the degree of crystallinity go down with increasing filler concentration. Tensile modulus goes up as result of filler loading while the tensile strain at break goes down. As the result, brittleness B goes up somewhat, but overall the values of B are quite low. With one exception, residual depth in scratch resistance testing decreases as a consequence of introduction of the fillers. Addition of unmodified wood results in increasing dynamic friction, chemical modification of wood particles results in lowering friction. Combination of focused ion beam milling with scanning electron microscopy shows clearly positive effects of modification on adhesion between the phases.